(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
This study investigates the impact of rubric-based assessment on EFL students’ writing performance at Sebha University and explores instructors’ perceptions of its effectiveness. A mixed-methods approach was adopted, utilizing a quasi-experimental design and a descriptive survey. To ensure greater scoring objectivity, inter-rater reliability was calculated. The findings revealed a statistically significant improvement in students’ writing quality after the intervention, with a substantial effect size. Furthermore, teachers expressed positive attitudes toward the use of rubrics, highlighting their role in enhancing grading transparency and fairness. Despite these benefits, the study was limited by a small sample size and the absence of a control group, as well as time demands associated with rubric implementation and training. The study recommends integrating rubric-based assessment into higher education to enhance assessment practices and support students’ self-regulation skills.